Pengaruh Penggunaan Alat Peraga Pembentukan Urine Terhadap Kemampuan Literasi Sains Siswa SD - Anggreni, Monica; Ariefka, Reza (ALACRITY : Journal of Education, 2025)
In Indonesia, according to the 2022 PISA results, students' scientific literacy is in a low category, equivalent to the results obtained in 2006, and is ranked 68th out of 81 countries. Based on existing problems, innovation is needed to increase scientific literacy, one of which is using science teaching aids. This research examines the effect of using urine formation teaching aids on the scientific literacy abilities of grade IV students at SDN 2 Riang Bandung. In this research, the method used is a quantitative method in which the research experiments with a one-group pretest-posttest design, and the data collection techniques are in the form of observation, tests, and documentation. The data processing technique was obtained through test instrument testing and hypothesis testing. From processing this data, the normality test value was obtained, which had a pretest value of 0.171, then the post-test value was 0.051, which stated that the value was normal. Then the homogeneity test which has a pretest value of 0.075 which is explained that the value is greater than 0.05 which is stated that the value is homogeneous. Finally, the paired sample t-test has a pretest value of 0.000, which means the value is smaller than 0.05. Thus it can be stated that the null hypothesis value (Ho) is rejected and the hypothesis (Ha) is accepted. Hypothesis testing proves that using urine formation props on the scientific literacy skills of elementary school students has a great influence on class IV of SDN 2 Riang Bandung.